TIME-DEPENDENT SURFACE TOPOGRAPHY IN A COUPLED CRUST-MANTLE CONVECTION MODEL - Pysklywec R.N.; Shahnas M.H. (My University, 2003)
Recent geodynamic research has shown that convective flow in the mantle may have an important role in the development of long-wavelength surface topography. This flow-induced ‘dynamic topography’ is usually derived from mantle convection models by computing the vertical component of hydrodynamic stress at the top of the model and assuming the stress is compensated by deflection of the surface. However, these models have generally ignored the presence of an overlying buoyant crust and its deformational response to the mantle flow. We consider the effects of horizontal convective forcing on the crust and investigate how this crust/lithosphere deformation interacts with the vertical component of mantle flow-induced subsidence/uplift at the surface. In particular, we test the response of various rheologies of the crust and mantle lithosphere to an episode of mantle downwelling. The evolution of crustal thickness and topography is tracked using thermomechanical numerical models of the crust–mantle system with a free surface upper boundary. A strong crust (ηc= 2.5 × 1025 Pa s) does not experience significant internal deformation and subsides above a mantle downwelling. For a weaker crust (ηc < =1023 Pa s), descending mantle flow initially induces subsidence, but there is an inversion to surface uplift as crustal thickening induced by convergent mantle flow overcomes the dynamic subsidence. The presence of a strong mantle lithosphere, however, may effectively shield a weak crust from deformation imposed by the underlying horizontal mantle convective stresses. With temperature-dependent rheologies in the model, the interplay of the vertical/horizontal mantle forcings with the thermal evolution of the crust results in a highly time-dependent signal of topography. Subsequent to crustal thickening and uplift, the system may undergo rapid topographic subsidence and crustal thinning by localized channel flow in the hot and weak lower crust. These results suggest an alternative interpretation for the development of mantle-flow induced topography in certain tectonic environments.
Keywords: geodynamics; lithospheric deformation; mantle convection; numerical techniques; plate tectonics; topography